STRUKTURASI KONFLIK PENYESUAIAN TEMUAN AUDIT MELALUI PENELITIAN HUBUNGAN ANTARA AUDITOR DENGAN KLIEN - Abigail, Jane; Meiden, Carmel (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2016)
The purpose of this study is to understand the meaning of structuration adjustment audit findings conflict, to examine the terms of the roles and relationships between the auditor and management of their clients in the process of audit completion. Structuration theory states that the perpetrator and interrelated structure, no structure without actors, as there is no action without structure. The object of this research is a public accounting firm and the client where researchers work, as the number of informants in this study is five people. This study uses a phenomenological approach, because this research is directly related to the symptoms that occur in the sphere of organized human interaction. The method used in this research is qualitative. The results of the study reflect that the relationship between the auditor and the client has two principal types, namely proactive and reactive. Clients tend to perform reactive action during conflicts in the adjustment of the audit findings, so that there will be formal andinformal actions in these interactions that will influence the outcome of the audit.